When the well runs slow: how declining well yields and pumping interference reshape irrigation in the High Plains Aquifer - Haroon Bin Farrukh, Syed (My University, 2025)
Groundwater is a critical resource for agricultural resilience against climate change and surface water variability, yet depletion poses significant risks to irrigation sustainability and food security. A key concern is declining well yields—the rate at which water can be extracted—which constrain farmers’ ability to meet crop water demand at critical stages of growth. While prior studies recognize the importance of well yields in irrigation decisions, empirical evidence on their impact remains scarce. Additionally, economic analyses of pumping externalities overlook well interference spillover effects despite their hydrological and economic significance. This study address three key gaps in the literature: (1) estimating well yields and analyzing their spatial and temporal variation across the High Plains Aquifer region of Kansas, (2) evaluating farmers’ irrigation response to limited well yields along extensive (irrigated acreage), indirect intensive (crop choice), and direct intensive (water application depth) margins, and (3) estimating well yield spillover effects and analyzing how these affect water use. Using a 24-year panel dataset of over 6000 wells, we find substantial well yield declines (up to 33%) in high depletion districts, driven by reduced saturated thickness. Econometric analysis reveals that a 100 GPM decrease in well yield decreases irrigated area by 13.5 acres, water application depth by 0.47 inches and the probability of planting corn by 3 percentage points. Water use adjustments are most responsive at low to moderate well yields (250-750 GPM), with three quarters of adjustment in water use occurring at the extensive margin. Furthermore, well interference generates spillover effects on the neighboring farmers, with median well yield reductions ranging from 6% in low transmissivity areas to 20% in high transmissivity areas. High well density (10 neighbors) can reduce water use by 22.3% compared to isolated wells. Future groundwater governance could benefit from spatially explicit regulations that account for hydrological constraints revealed by well interference effects. Future research should explore how well yields influence efficient irrigation technology adoption, agricultural land values and market-based water trading mechanisms.
Keywords: Groundwater; Well yield; Well interference; Water use; High Plains Aquifer